PENGARUH STORE ATMOSPHERE, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN: (Studi Kasus di Padda Coffe Kota Batu) - murni, Tri; Yolana Nabilla, Hanna (STIA MALANG, 2024)
The phenomenon of the emergence of coffee shop businesses in Indonesia has recently experienced rapid development. Changes in lifestyle and consumer tastes who want fast service and are supported by the development of modern technology have had a big impact on the culinary industry, including cafes. Access to product information and social media makes it easier for business actors to sell their products. This moment can be utilized as well as an opportunity for business people and cafe industry players to develop their businesses. Store atmosphere, quality products and quality service also have an important role in determining consumer satisfaction. The aim of this research is to find out how the store atmosphere, product quality and service quality influence consumer satisfaction. iThis type of research is explanatory research with an quantitative approach, data collection methods are carried out through questionnaires, observations and interviews. i iSample collection was determined using the Lemeshow formula, because the population in this study is unknown with a total of 100 respondents who are Padda Coffee consumers. The data analysis method used is multiple linear irregression analysis. iThe results of this research show that: 1) Store Atmosphere has a positive and significant influence on consumer satisfaction with a calculated result of 3.877. 2) Product quality has a positive and significant impact on customer satisfaction with a t-count of 2.871. 3) Service quality has a positive influence on customer satisfaction with a value of 4.274. Based on the calculation of the coefficient of determination, it is known that the store atmosphere variables, product quality and service quality jointly influence consumer satisfaction with a contribution of 75.2%